Effect of The Composition of TiO2 Additives on The Physical and Magnetic Properties Crystal Structure and Microstructure of BaFe12O19 Magnetic Ceramics - Ramlan Ramlan; Endah Puspita (Department of Physics, Sebelas Maret University, 2023)
In this research, the manufacture of barium hexaferrite (BaFe12O19) magnetic ceramics and the addition of titanium dioxide (TiO2) additives with variations of 0%: 0.3%: 0.6% and 0.9% used the powder metallurgical method. The characterization used in this study is the measurement of density, porosity, X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Vibrating Sample Magnetometer (VSM), and Impulse Magnetizer K-Series. Based on the results of density and porosity measurements, the highest values were 4.95 g/cm3 and 5.45%, respectively. XRD results showed the formation of a BaFe12O19 phase with some impurities at 0% (Fe2O3), 0.3% and 0.9% (Ti6O11), and 0.6% (Ti4O7). The SEM results showed that the morphology of TiO2-BaFe12O19 was quite homogeneous, and the size and cavity ranged from 0.5 – 1.5 μm and 0.25 – 0.9 μm, respectively. VSM results show Mr, Ms, Hc, and Bhmax values of 1,489 kG, 3,235 kG, 1,758 kOe, and Bhmax of 0,867 MGOe, respectively. The results of the Impulse Magnetizer K-Series show the maximum and lowest magnetic flux values of 272.65 gauss and 218.10 gauss at 0.6% and 0% variation, respectively.